Sensitiveness of stock market returns to macroeconomic determinants; an empirical study on the pharmaceutical industry of Dhaka Stock Exchange - Tasrin, Ibnat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.